Product development and cost analysis of fabricating the prototype of roller clamp in intravenous (I.V) tubing medical devices using fused deposition modeling (FDM) technology - Wan Yusoff, Wan Ahmad Yusmawiza (2018)
The main aim of this research is to develop a new prototype and to conduct cost analysis of the existing roller clamp which is one of parts attached to Intravenous (I.V) Tubing used in Intravenous therapy medical device. Before proceed with the process to manufacture the final product using Fused Deposition Modeling (FDM) Technology, the data collected from survey were analyzed using Product Design Specifications approach. Selected concept has been proven to have better quality, functions and criteria compared to the existing roller clamp and the cost analysis of fabricating the roller clamp prototype was calculated.